Slogans and logos as brand signals within investment promotion. Issue 2 (12th October 2020) - Wilson, Rick T.
Abstract : Purpose: The purpose of this research is to understand how brand-building is used to lend credibility to investor information and to differentiate countries competing for foreign investment. Brand signals, such as slogans and logos, are frequently used by governments and their investment promotion agencies to enhance the presentation of information to potential investors interested in acquiring or establishing a business within their country. Yet, little is known about how governments use brand building to foster professionalism and convey their expertise in international expansion assistance and differentiate themselves from one another in an investment promotion context. Design/methodology/approach: This research content analyzes the slogans and logos found in 55 months of print advertising and on the websites of 181 countries engaged in investment-seeking activities. Findings: The research finds that slogans and logos are frequently used across both samples, but slogan use is greater in print advertising than on the Web, which is likely because of the greater effort required to develop an advertising campaign than to maintain a website. Regardless of medium, logo use is greater than slogan use. In the sample, slogans tended to be generic or undifferentiated and do not appear to facilitate brand credibility. However, logos were better designed than slogans and incorporated more territorial and cultural symbols and elements of expertise. Originality/value: This study provides for a deeper understanding of investment promotion, especially, as it relates to brand building both on the Web and in print advertising. It also extends the author's understanding of brand building within a specialized area of business-to-business organizational buying. From a managerial perspective, the research highlights the need for differentiated slogans and for logos using territorial and cultural symbols to better assist governments with appearing more professional, conveying expertise and differentiating their country from potential rivals.